Comparative analysis of Three Metaheuristics for Solving the Travelling Salesman Problem - Bouzidi, Safaa; Essaid Riffi, Moahmmed; Bouzidi, Abdelhamid (Transactions on Engineering and Computing Sciences, 2017)
this research paper aims to do a comparative study of three recent optimization metaheuristic approaches that had been applied to solve the NP-hard optimization problem called the travelling salesman problem. The three recent metaheuristics in study are cuckoo search algorithm, cat swarm optimization algorithm and bat-inspired algorithm. To compare the performances of these methods, the three metaheuristics are applied to solve some benchmark instances of TSPLIB. The obtained results are collected and the error percentage is calculated. The discussion, will present which method is more efficient to solve the real application based on the travelling salesman problem.